Ampliação da jornada escolar do Colégio Estadual Industrial de Francisco Beltrão/PR: análise da proposta curricular de educação de tempo integral de turno único - Setti, Valdenice Maria da Silva (2019)
. This research proposes to analyze the curricular proposal of the Industrial State High School of Francisco Beltrão – PR, in its specificity as a curricular proposal of E.T.I. single shift. The main objective is to understand how the process of implementation of said curricular proposal occurred, analyze how it was idealized and organized, to distinguish between educational norms and pedagogical and curricular guidelines, in the context of the educational politic of the Union and the State Parana for the E.T.I., normalized and oriented the curricular proposal of the Industrial State High School; highlighting also the issues that cover the school curriculum in generatly. It´s a qualitative research that uses the case study as a method, mainly because it implies in contemporary events, beside bibliographic research, used as a research instrument, semi structured interviews for providing important data, that when they are described and analyzed are part of the composition of the discussions in the body of the text. The work was divided in three chapters. In the first chapter, some questions about the historical course on the school and its relation with the E.T.I in Brazil and the Parana, reporting some school experiences as CECR, CEU, CIEP e CAICS. In the second chapter it emphaizes questions of analysis on the political pedagogical process of construction of the full-time education Project of the Industrial school´s sole shift. The third chapter, it discusses the staff, the physical structure, the initial and continuing training, the timetable and the duration of the students‟ stay in the school environment. It also describes the dilemmas of curricular practice, pointing out the challenges and improvements of pedagogical and administrative management. This research presents relevant approximations for the implementation of the expansion of the school time journey. It´s necessary to offer Integral Education not as extra shift, with ruptures of temporal sequences, but with curricular integrality, with articulation of times and spaces. The school community of the State Industrial School has taken up the challenge of building an integrated curriculum for the implementation of E.T.I, but it needs more financial investments, physical and human resources and this research does not answer all the questions about the topic.